Acoustic approach of the dynamic and spatial distribution of small pelagic marine resources inside Sénégalo-mauritanian upwelling - (:unkn) unknown (My University, 2017)
Along the coast of North-West Africa, among the richest waters over the word, fish supply is important at both socio-economic and cultural levels. In this region, the small pelagic fish are the most abundant marine resources and are monitored using hydroacoustic stock assessment methods since more than three decades. These surveys have allowed providing to local authorities a sound scientific basis for deciding about the management of pelagic fisheries. A specific challenge is to know the representativity of these surveys with respect to the stocks targeted. In this work, we confirm this representativity for Sardinella aurita stock while for S. maderensis, a part of the stock could have not been sampled and for pour Ilisha africana and Ethmalosa fimbriata these surveys are not the best tool. Furthermore, Northward shifts in the distribution of sardinella in the Canary Current Large Marine Ecosystem are recorded in this work and have been attributed to the redistribution of upwelling intensity and productivity, resulting in the abundance of sardinella decreasing in the inter-tropical coastal region. Here for the first time using independent observational time series, we report a robust northward shift in S. aurita since 1995 and attribute it to the strong ocean warming in the region. The observed spatial shifts in biomass in the last 20 years are of the same order of magnitude as those recorded for surface isotherms. Such changes will impact policy considerations in the management of food security in several West African countries and should be considered with respect to “Intended Nationally Determined Contributions”.
Keywords: African Research